(untitled) (Al-Ilmu, 2025)
The rapid growth of social media has transformed the learning ecosystem of Generation Z, who rely on visual, fast, and interactive content and increasingly encounter Islamic Religious Education (PAI) through digital platforms. This study responds to the limited research on how challenge-based learning can be systematically integrated into social media environments most used by Gen Z, such as TikTok, Instagram, and YouTube Shorts. The research aims to analyse the characteristics, opportunities, and risks of social media challenge-based PAI learning for Generation Z and to identify the pedagogical, technological, and value-oriented elements required for its effective implementation. A Systematic Literature Review (SLR) was conducted using the PRISMA protocol. Searches in major academic databases for the period 2014–2024 produced 86 records; after screening, eligibility assessment, and critical appraisal, 14 articles were included and synthesised thematically. The findings show that social media challenge-based learning can significantly increase student engagement, religious digital literacy, collaboration, and internalisation of Islamic values when activities are designed to be experiential, reflective, and aligned with Gen Z’s digital habits. However, the results also highlight serious challenges related to misinformation, algorithmic bias, superficial learning, and gaps in digital literacy between teachers and students. The study concludes that the success of this model depends on teacher capacity in content curation, digital ethics guidance, and challenge design, supported by clear institutional policies on safe and moderate social media use. The article offers an integrated conceptual understanding that can guide future empirical applications of challenge-based PAI learning for Generation Z.